Peningkatan Kualitas Pelayanan Pengelola Penginapan di Tahura KGPAA Mangkunagoro I - Herman NK Paninggiran; Agnesia Putri K; Bram Arvianto; Dinar Anggit Wicaksana (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
KGPAA Mangkunagoro I Grand Forest Park (Tahura) is a popular nature-based tourist destination, especially during major events. However, the limited capacity of its two official lodgings often fails to accommodate all visitors. As an alternative, tourists are directed to stay in nearby residents' homes through a guest house or homestay concept. To improve the quality of services and lodging management, a training program was conducted for staff and homestay owners. This training aimed to enhance participants' skills in customer service, effective communication, and professional complaint handling. A total of 15 participants, consisting of accommodation staff and homestay owners, took part in the program. The training employed a combination of theoretical sessions, interactive discussions, real-life simulations, and hands-on practice at the lodging sites. Evaluation results showed a significant improvement in participants’ competencies, reflected in a post-test questionnaire score of 97%. It is expected that this training will contribute to raising the standard of hospitality services in the Tahura area and ultimately increase the number of visitors to the region.